Clinical hematology : principles, procedures, correlations - Lotspeich-Steininger, Cheryl A. ;Stiene-Martin, E. Anne ;Koepke, John A. (Philadelphia, Pennsylvania : J.B. Lippincott Company, 1992)
Intended for students and practitioners in clinical laboratory science, this text stresses the physiology of blood cells, the etiologies of haematologic diseases and the theoretical basis of laboratory procedures.
Introduction to haematology; the erythocytes; erythrocyte abnormalities (non-malignant); the leukocytes; leukocyte abnormalities (non-malignant); special haematologic evaluations; malignant myeloproliferative disorders; malignant lymphoproliferative disorders; instrumentation for haematologic evaluation; quality control and assurance in haematology; introduction to haemostasis; management.
Keywords: HEMATOLOGY